Relationship between innovation capability, innovation type, and firm performance - R.P. Jayani Rajapathirana; Yan Hui (Journal of Innovation & Knowledge (JIK), 2018)
Insurers are well versed in the litany of challenging conditions facing the sector. These challenges are economic, political, regulatory, legal, social, and technological. As a result of those pressures, the industry is experiencing increasing competition, muted growth, and an excess of capital. The increased connectivity among household and workplace devices, the development of autonomous vehicle and the rising threat of cyber attacks are transforming the way people live and risk they need to mitigate with insurance products. Insurers need to adopt their business models address the changes which can be threatening to the growth of the industry (Deloitte, 2017). Innovation is widely regarded as pinnacle success factor in highly competitive and global economy. An innovation perspective draws a clear picture of future opportunities that lie ahead. The main purpose of this paper is to explore the relationship among innovations capability, innovation type and on the different aspect of firm performance including innovation, market and financial performance based on an empirical study covering insurance industry in Sri Lanka. The research framework developed in this study was tested 379 senior managers of insurance companies. The empirical verification of assumption of this model has given evidence to confirm the relationship between innovation capabilities; innovation efforts and firm performance are significant and strong. The results of this study could lead effective management of innovation capability which helps to deliver more effective innovations outcomes to generate better performance and it would be benefits for management of the insurance companies.
Keywords: M10; O31; O39; 650; Innovation capability; Innovation type; Innovation performance; Market performance; Financial performance